2006
DOI: 10.1063/1.2337993
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics in thin-slice Nd:YAG ceramic lasers: Coupled local-mode laser model

Abstract: The authors propose a coupled spatially distributed local-mode laser model for understanding self-induced high-speed modulations in Nd:YAG ceramic lasers with laser-diode end pumping, which critically depend on pump positions. In addition to complicated high-speed modulations, quasiperiodic and chaotic relaxation oscillations have been demonstrated experimentally and reproduced by numerical simulation of the model of coupled local-mode lasers. Q-switching-like periodic spiking pulsations have been also observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Transient liquid phase (TLP) sintering of CaF 2 additive on the densification behaviors and microstructural development of AlN ceramics are investigated [295]. It is found that 1 wt% CaF 2 can effectively promote densification process.…”
Section: Aluminum Nitride (Aln)mentioning
confidence: 99%
“…Transient liquid phase (TLP) sintering of CaF 2 additive on the densification behaviors and microstructural development of AlN ceramics are investigated [295]. It is found that 1 wt% CaF 2 can effectively promote densification process.…”
Section: Aluminum Nitride (Aln)mentioning
confidence: 99%
“…It thus appears that the lasing transverse mode should be split into local modes having different frequencies, exhibiting dynamic instabilities. 4,5) In the case of laser B, on the other hand, linearly polarized oscillations were obtained in a single TEM 00 transverse mode, as shown in Fig. 2(b).…”
mentioning
confidence: 91%
“…In this section, our experimental results concerning lasing pattern formations due to grain boundaries and the resultant dynamic instabilities observed in Nd:YAG ceramic lasers (Kawai et al, 2004;Narita et al, 2005;Otsuka et al, 2006) are reviewed.…”
Section: Formation Of Local Transverse Modes and Associated Dynamic Ementioning
confidence: 99%